Application of modified silica gel in the process of trypsin immobilization - Miłek, Justyna; Kwiatkowska-Marks, Sylwia; Trawczyńska, Ilona (Technical Sciences, 2019)
The paper presents the use of modified silica gel for the production of immobilized trypsin from bovine pancreas. Silica gel was modified with 3-aminopropyltriethoxysilane, followed by glutaraldehyde. The influence of stirring time on activity of the prepared biocatalyst was determined for individual stages of the modification. Activity of both native and immobilized trypsin was measured using Kunitz method. At the temperature of 55℃ and pH 7.6 native and immobilized trypsin onto modified silica gel indicate optimum activity. The influence of multiple recycling and storage time on activity of immobilized trypsin was tested. After fourteen days of storage at the temperature of 4℃ immobilized trypsin exhibits 75% of its initial activity.